Challenges of Policy Reform on Government Accounting in Indonesia : Response to Changing Global Dynamics - Ahmadi Aidi; Redjeki Agoestyowati; Imam Susanto; Supriyono Supriyono; Dinda Aulia Rahman (Yayasan Ilomata, 2021)
The discussion in this article is about changes in government accounting, a significant change from government accounting in Indonesia is from cash-based accounting to cash-based accounting towards accruals (cash toward accruals), to full accruals. The writing method used is a literature study with a qualitative approach . The research method used is a literature study with a qualitative approach. Sources of data were obtained through searching articles related to accounting policies carried out by the government. The purpose of this study is to identify and analyze the challenges in reforming government accounting policies in Indonesia. The finding of the study that state that the government needs to prepare financial statements in accordance with Law No. 17 of 2003 which refers to Government Accounting Standards (SAP/standar akuntansi pemerintahan). As a derivative of this regulation, the government has issued Government Regulation Number 24 of 2005 which was updated with Government Regulation Number 71 of 2010 concerning Government Accounting Standards (SAP). Practical implications there are , the basis of government accounting records changed from a cash basis to a cash basis to an accrual basis and to a full accrual basis.